Biological removal of selenate and ammonium by activated sludge in a sequencing batch reactor. (April 2017) - Mal, J.; Nancharaiah, Y.V.; van Hullebusch, E.D.; Lens, P.N.L.
Graphical abstract: Highlights: Selenate bioreduction by alternating anaerobic – aerobic conditions in a SBR. Ammonium was removed by simultaneous nitrification and denitrification. Majority of selenium was entrapped in activated sludge as Se(0). First report on the simultaneous removal of Se(VI) and NH4 + -N by activated sludge. Abstract: Wastewaters contaminated by both selenium and ammonium need to be treated prior to discharge into natural water bodies, but there are no studies on the simultaneous removal of selenium and ammonium. A sequencing batch reactor (SBR) was inoculated with activated sludge and operated for 90 days. The highest ammonium removal efficiency achieved was 98%, while the total nitrogen removal was 75%. Nearly a complete chemical oxygen demand removal efficiency was attained after 16 days of operation, whereas complete selenate removal was achieved only after 66 days. The highest total Se removal efficiency was 97%. Batch experiments showed that the total Se in the aqueous phase decreased by 21% with increasing initial ammonium concentration from 50 to 100 mg L −1 . This study showed that SBR can remove both selenate and ammonium via, respectively, bioreduction and partial nitrification-denitrification and thus offer possibilities for treating selenium and ammonium contaminated effluents.